The Effect of Calcium Compounds Bone Graft Synthesized from Blood Cockle Shells (Anadara granosa) with Sintering Time Variation in Fibroblast Proliferation on Socket Healing Process - Firda Dean Yonatasya; Widyasri Prananingrum; Meinar Nur Ashrin (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2019)
Backgorund: Anadara granosa shells can be converted into calcium compounds in the form of hydroxyapatite (HA), tricalcium phosphate (TCP), and calcium carbonate (CaCO3) by hydrothermal method. These calcium compounds have the potential to increase the proliferation of fibroblast cells in the socket healing process. Purpose: The aim of this study was to determine the effect of calcium compounds from the synthesis of Anadara granosa with variations in sintering time against proliferation of fibroblast cells in socket healing. Materials and Methods: 36 Wistar rats were divided into control group (K1, K2), and treatment group (P1a, P1b, P2a, P2b) which was applied by bone graft with the sintering time 6 and 12 hours on the socket incisor of the left mandible. On the 7th and 14th days, the mandibular bone was cut transversely and stained. Observation of the number of fibroblast cells use 400x magnification with 3 visual fields and the mean was calculated. Data were analyzed using the Kruskal-Wallis test. Results: The mean number of fibroblast cells in groups K1, K2, P1a, P1b, P2a and P2b respectively is 23.50; 30,16; 28.94; 34.22; 30,16; and 37.50. There were significant differences in all groups, except K2-P1a, K2-P2a, and P1a-P2a. Conclusion: Calcium compounds bone graft from the synthesis of Anadara granosa with sintering time of 6 and 12 hours affect the proliferation of fibroblast cells in socket healing. Bone graft with a sintering time of 12 hours can increase fibroblast cell proliferation more effectively.